Implementation of Muhammadiyah Orphanage - Lendriyono, Fauzik (2014)
Muhammadiyah is an Islamic based community organization and one of the biggest religious community organization in Indonesia.As their contribution in community, Muhammadiyah works on three charitable works, which are: Education, Health service, and Orphanage.These three charitable works has been well developed and give a big contribution in Indonesia building.The orphanage management in Muhammadiyah has a unique characteristic. These orphanages are built, managed, and developed by the people of Muhammadiyah voluntarily.The spirit of Orphanage management in Muhammadiyah is based on what has been written inside Surah Al-Maa’uun in the Holy Quran.This spirit that brings out Muhammadiyah as a religious community organization that own the largest numbers of Orphanage in the world. Unfortunately, the numbers of Orphanage in Muhammadiyah is less supported by its management and service quality.Those orphanage have not been yet fully apply a proportional and professional management. The analysis of Muhammadiyah orphanage in Malang Raya in regard to Quinn’s typology, could be explained as follow.First, Orphanage with group culture.This group culture features internal support from the manager, the caregivers, and the orphans.It is a dynamic orphanage that focus on the group loyalty and protection.The tendency of the manager, the caregivers, and the orphans is to protect and ask commitment from each sides.Second is the orphange with a hierarchy or rational developing model.This kind of orphanage might not care too much about love and caring for the orphans, but they pay more attention in creating new things that could develop the orphanage.They tend to obey any instructions from their leader and search for the aims of organization in order to be benefited materially.